Evaluation of anti-methicillin-resistant staphylococcus aureus property of zerumbone - Fadhel Abbas Albaayit, Shaymaa; Maharjan, Rukesh; Abdullah, Rasedee; Mohd Noor, Mohd Hezmee (University of South Bohemia, 2022)
Context and objective: Zerumbone has been reported to exert anti-microbial effects, but the mechanism by which the compound exerts its action is not known. Thus, this study aimed to investigate the mechanism of action of zerumbone against methicillin-resistance Staphylococcus aureus (MRSA), using the atomic force microscopy (AFM), scanning electron microscopy (SEM), and flow cytometry techniques. Methods: MRSA (NCTC 13277) cell viability was determined using the microplate AlamarBlue assay. AFM and SEM were used to determine the morphology of zerumbone-treated MRSA cells. Flow cytometric analysis was used to determine the effect of zerumbone on bacterial membrane permeability and membrane potential, using the propidium iodide (PI) staining method, membrane potential-sensitive fluorescence probe, and DiBAC4(3) dye. DCFDA dye was used to determine the generation of reactive oxygen species (ROS) by MRSA. Results: Zerumbone significantly inhibited MRSA growth with a minimum inhibitory concentration (MIC) of 125 µg/ml. The AFM analysis showed that zerumbone caused leakage of cytoplasmic content from the bacterial cells. Ultrastructure analysis showed small colonies of the bacteria with pores on the membrane surface. There were increases in zerumbone-treated MRSA PI and DiBAC4(3) fluorescence, indicating an increase in cell membrane permeability and a decrease in membrane potential that culminated in the loss of membrane structural integrity and bacterial death. Based on DCFDA dye analysis, zerumbone also reduced ROS production by MRSA. Conclusions: Zerumbone exerts anti-MRSA effects by causing membrane depolarization, increasing membrane permeability, and finally disrupting cell membrane and bacterial killing.